Analisis Preferensi Bahan Bakar Minyak Subsidi dan Non Subsidi Di Purwokerto - Purnomo, Sodik Dwi; Setiawan, Heri; Danuta, Krisnhoe Sukma; Zuhaena, Fatwa; Adhitya, Bagus (Universitas Batanghari Jambi, 2024)
The need for fuel oil for the transportation sector increases every year, while non-renewable energy reserves are increasingly depleting. Subsidized fuel oil is seen as not on target, the heavy burden of fuel oil subsidies limits fiscal space so that APBN allocations for other development sectors are limited. The increase in fuel prices is one of the considerations in choosing fuel. This research aims to analyze the factors that influence fuel oil preferences in North Purwokerto. The sample in this study amounted to 96 respondents who were calculated using the Lemeshow formula. This research uses logistic regression analysis. The results of the logistic regression analysis show that vehicle age, engine capacity, income, gender, and volume of fuel use have a significant effect on preferences for subsidized and non-subsidized fuel oil in North Purwokerto. Meanwhile, type of vehicle, number of family dependents, type of work, regional origin and social status do not have a significant effect on preferences for subsidized and non-subsidized fuel oil in North Purwokerto. The implication of this research is the need to increase consumer knowledge about the use of fuel oil that is adjusted to vehicle conditions. The government can make policies so that subsidized fuel can be received by people who are entitled to need it.